2013
DOI: 10.1242/jeb.087692
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of ventilation and brain metabolism to ammonia exposure in rainbow trout,Oncorhynchus mykiss

Abstract: SUMMARYAmmonia has been documented as a respiratory gas that stimulates ventilation, and is sensed by peripheral neuroepithelial cells (NECs) in the gills in ammoniotelic rainbow trout. However, the hyperventilatory response is abolished in trout chronically exposed (1+ months) to high environmental ammonia [HEA; 250μmoll −1 (NH 4 ) 2 SO 4 ]. This study investigates whether the brain is involved in the acute sensitivity of ventilation to ammonia, and whether changes in brain metabolism are related to the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…All fish were fasted for at least 3 days prior to experimentation to minimize the influence of feeding on ammonia metabolism. For methodological details, the reader is referred to our published studies on rainbow trout (Zhang and Wood, 2009;Zhang et al, 2011Zhang et al, , 2013 and dogfish sharks (De Boeck and Wood, submitted for publication). Detailed methods are described below only for the new studies reported in the present paper.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All fish were fasted for at least 3 days prior to experimentation to minimize the influence of feeding on ammonia metabolism. For methodological details, the reader is referred to our published studies on rainbow trout (Zhang and Wood, 2009;Zhang et al, 2011Zhang et al, , 2013 and dogfish sharks (De Boeck and Wood, submitted for publication). Detailed methods are described below only for the new studies reported in the present paper.…”
Section: Methodsmentioning
confidence: 99%
“…At present, we favor the idea that internal receptors are responsible for the bulk of the responsiveness, for two reasons. Firstly, the hyperventilatory response to internal ammonia injections is essentially immediate (McKenzie et al, 1993;Zhang and Wood, 2009), whereas the response to waterborne HEA takes 5-10 min and increases progressively thereafter for some time (Zhang et al, 2011(Zhang et al, , 2013. Secondly, as discussed in Section 3.4, it is difficult to see how ventilatory responsiveness to waterborne ammonia alone would be adaptive.…”
Section: Are There External Ammonia Receptors Controlling Ventilation?mentioning
confidence: 99%
See 2 more Smart Citations
“…Different animals were used in the two treatments, and standard 6 h flux tests were run with 200 µmol l −1 ammonia (added as NH 4 HCO 3 ) in the water. The MSOX dose (60 mg kg −1 ) was approximately 10-fold greater than routinely used in teleosts (Sanderson et al, 2010;Zhang et al, 2013), but glutamine synthetase is more abundant in elasmobranchs (Kajimura et al, 2006). In a preliminary experiment with one animal, this dose proved not to cause mortality but did cause a slow decline in urea-N excretion rate after 48 h. Therefore, the 6 h tests were run at 35-41 h after injection, a time selected to avoid any secondary consequences due to internal urea declines.…”
Section: Experiments V: Effect Of Msox On Ammonia-n Uptakementioning
confidence: 99%